THE ROLE OF CUSTOMER SATISFACTION IN MEDIATING THE EFFECT OF SERVICE QUALITY ON THE INTENTION TO REUSE(A Study on JNE Express Customers in Denpasar City) - I Made Pradnya Raditya Putra; Ni Ketut Seminari (Adisam Publisher, 2025)
Abstract: The development of increasingly competitive expedition services requires companies to understand the factors that affect customer behavior, particularly the intention to reuse services. This study aims to analyze the effect of service quality on the intention to reuse among JNE Express customers in Denpasar City, with customer satisfaction as a mediating variable. The study involved 120 respondents selected using the purposive sampling method. Data were collected through questionnaires and analyzed using Path Analysis, Classical Assumption Tests, the Sobel Test, and the Variance Accounted For (VAF) test. The results indicate that service quality has a positive and significant effect on the intention to reuse, service quality has a positive and significant effect on customer satisfaction, customer satisfaction has a positive and significant effect on the intention to reuse, and customer satisfaction partially mediates the effect of service quality on the intention to reuse. These findings reinforce the Expectation Confirmation Theory (ECT), which explains that improvements in perceived service quality enhance customer satisfaction, ultimately encouraging customers’ intention to continue using JNE Express services in Denpasar City. Keywords: Service Quality, Customer Satisfaction, Intention to Reuse